Academic Self-Efficacy and its relation to Academic Boredom among Umm Al-Qura University female students - Hammdi, Makiah Abdo (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the relationship between academic self-efficacy and academic boredom among Umm Al-Qura University female students using the descriptive correlative approach. Ghanem’s academic self-efficacy scale (2007), developed and standardized by Al-Qurashi (2016); and Bashayreh’s academic boredom scale (2011) were applied to the study sample of (237) female students of various academic levels. The results of the study showed a statistically significant positive correlation between both the academic self-efficacy and its dimensions (general self-efficacy- specific self-efficacy) and academic boredom among the female students. The study also revealed that the level of academic self-efficacy and the level of academic boredom were also average among the female students. The results concluded that there are no statistically significant differences in academic self-efficacy in general, its dimensions, and the academic boredom among the female students depending on the academic level variable. The study recommends utilization of the activities that support and promote academic self-efficacy; the creation of educational and guidance programs for the development of Academic Self-efficacy among university students; in addition to working on the inclusion of activities in the curricula; and increasing attention to teaching methods in order to reduce academic boredom among the students.